Six-month longitudinal immune kinetics after mRNA-1273 vaccination: Correlation of peak antibody response with long-term, cross-reactive immunity - Choi, Min Joo; Heo, Jung Yeon; Seo, Yu Bin; Yoon, Young Kyung; Sohn, Jang Wook; Noh, Ji Yun; Cheong, Hee Jin; Kim, Woo Joo; Choi, Ju-yeon; Kim, Hwa Jung; Lee, Young Jae; Lee, Hye Won; et al. (Frontiers in Immunology, 2023)
Background: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants and the persistence of the pandemic, even with mass coronavirus disease 2019 (COVID-19) vaccination, have raised questions about the durability of immunity and extent of cross-reactive immunity after vaccination. This study aimed to characterize the humoral and cellular immunity response of the mRNA-1273 vaccine using a prospective longitudinal cohort. Methods: We recruited 177 young SARS-CoV-2 infection-naive adults. Two doses of mRNA-1273 vaccine were administered at 28-day intervals, and blood samples were collected at five time points: pre-vaccination (T0), 4 weeks after the first (T1) and second dose (T2), and 3 months (T3) and 6 months (T4) after the first dose. Anti-SARS-CoV-2 spike protein (anti-S) IgG antibody, neutralizing antibody, and T-cell immune responses were evaluated. Results: The two-dose mRNA-1273 vaccination induced robust anti-SARS-CoV-2 antibody responses, which remained higher than the titers at T1 until T4. A higher peak anti-S antibody titer at T2 was associated with better cross-reactive immunity against Delta and Omicron variants and long-lasting (anti-S IgG and neutralizing antibody) humoral immunity up to T4. The overall T-cell immune response was not correlated with peak antibody titers (T-lymphocyte subpopulation analysis was not performed). Conclusion: This study showed that an early strong antibody response is predictive of longer humoral immunity and better cross-reactive neutralizing immunity against Delta and Omicron variants.